2010
DOI: 10.1002/lary.20896
|View full text |Cite
|
Sign up to set email alerts
|

Is the width of the labyrinthine portion of the fallopian tube implicated in the pathophysiology of Bell's palsy?: A prospective clinical study using computed tomography

Abstract: Bell's palsy seems to usually coincide with the narrower fallopian tube of the patient. This anatomical detail, supported by previous MRI studies, seems to indicate that an asymmetry between the right and left fallopian tube might be a necessary pathogenetic mechanism for the development of a facial nerve edema into Bell's palsy in the narrower fallopian canal. More studies on large healthy populations are needed before a notable facial canal asymmetry is linked to a higher risk for developing Bell's palsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 22 publications
(38 reference statements)
2
44
0
1
Order By: Relevance
“…However, the cross section of the bony canal might vary in shape, including round, ellipsoid, kidney-shaped, and a triangular contour [3]. These findings suggest that the cross-sectional area, not the diameter, of the facial nerve canal in the temporal bone may be an important factor for mechanical compression and circulatory disturbance of the swollen facial nerve in Bell's palsy.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, the cross section of the bony canal might vary in shape, including round, ellipsoid, kidney-shaped, and a triangular contour [3]. These findings suggest that the cross-sectional area, not the diameter, of the facial nerve canal in the temporal bone may be an important factor for mechanical compression and circulatory disturbance of the swollen facial nerve in Bell's palsy.…”
Section: Discussionmentioning
confidence: 94%
“…Other features may include retroauricular pain which may extend into the neck and occiput, impaired tolerance of noise, and ipsilateral disturbance of taste [2]. Inflammation and edema of the facial nerve are considered fundamental parts of the pathogenesis in Bell's palsy [3]. Clinical studies have shown that corticosteroids significantly improve outcome compared with placebo, probably through their effects against inflammation and edema [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the extensive research, the etiology of Bell's palsy remains unclear [14]. However, positive evidence on the pathophysiology of this disease seems restricted to the edema of the facial nerve, which has been reported by contrast-enhanced MRI of the facial nerve 9-23 days after onset [10,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 98%
“…Former intraoperative observations gave the impression that the most likely site for conduction block and neural compression of the facial nerve is at the narrowest point of the facial canal, i.e. the entrance to the meatal foramen [14]. A bulbous swelling of the facial nerve proximal to this point [i.e.…”
Section: Introductionmentioning
confidence: 99%